Management of Avabahuka Through Mashadi Navana Nasya along with Bahya Snehana and Swedana w.s.r to Frozen Shoulder (AYUSHDHARA, 2024)
One of the Vatavyadhi induced by vitiated Vata and Kaphanubandha vata is Avabahuka. The symptoms of Avabahuka are similar to those of frozen shoulder, which is brought on by a rotator cuff lesion from the extracapsular cuff, such as partial tears in the supraspinatus tendon. Materials and Procedures: Shodhana Nasya has been recommended for a 49-year-old patient who has complained of discomfort and stiffness in the left shoulder joint and left lateral cervical region, as well as limited movement in these areas. Result: The patient's symptoms considerably subsided, including decreased neck and left shoulder joint discomfort and stiffness. Discussion: The patient received internal medicine along with Rukshana, Mukhabhyanga, Sarvang Abhyanga, sthanika Patra Pottali Swedana, Sarvanga Swedana, Mashadi Navana Nasya, and Upanaha, which helped to successfully treat the ailment.